Effects of nitrogen and phosphorus addition on microbial community composition and element cycling in a grassland soil. (December 2020) - Widdig, Meike; Heintz-Buschart, Anna; Schleuss, Per-Marten; Guhr, Alexander; Borer, Elizabeth T.; Seabloom, Eric W.; Spohn, Marie
Abstract: Microorganisms mediate nutrient cycling in soils, and thus it is assumed that they largely control responses of terrestrial ecosystems to anthropogenic nutrient inputs. Therefore, it is important to understand how increased nitrogen (N) and phosphorus (P) availabilities, first, affect soil prokaryotic and fungal community composition and second, if and how changes in the community composition affect soil element cycling. We measured soil microbial communities and soil element cycling processes along a nine-year old experimental N-addition gradient partially crossed with a P-addition treatment in a temperate grassland. Nitrogen addition affected microbial community composition, and prokaryotic communities were less sensitive to N addition than fungal communities. P addition only marginally affected microbial community composition, indicating that P is less selective than N for microbial taxa in this grassland. Soil pH and total organic carbon (C) concentration were the main factors associated with prokaryotic community composition, while the dissolved organic C-to-dissolved N ratio was the predominant driver of fungal community composition. Against our expectation, plant biomass and plant community structure only explained a small proportion of the microbial community composition. Although microbial community composition changed with nutrient addition, microbial biomass concentrations and respiration rates did not change, indicating functional redundancy of the microbial community. Microbial respiration, net N mineralization, and non-symbiotic N2 fixation were more strongly controlled by abiotic factors than by plant biomass, plant community structure or microbial community, showing that community shifts under increasing nutrient inputs may not necessarily be reflected in element cycling rates. This study suggests that atmospheric N deposition may impact the composition of fungi more than of prokaryotes and that nutrient inputs act directly on element-cycling rates as opposed to being mediated through shifts in plant or microbial community composition. Graphical abstract: Image 1 Highlights: Nutrient inputs differentially impacted microbial communities and element cycling. Soil pH and total organic carbon were main drivers of prokaryotic communities. DOC:DN ratio was the predominant driver of fungal community composition. Element cycling was controlled by abiotic factors, not by microbial community change. Microbial community change may not necessarily change ecosystem functioning.